1997
DOI: 10.1002/(sici)1098-2264(199711)20:3<282::aid-gcc9>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

dic(5;17): A recurring abnormality in malignant myeloid disorders associated with mutations ofTP53

Abstract: We have identified three unbalanced translocations involving chromosomes 5 and 17, der(5)t(5;17), der(17)t(5;17), and dic(5;17), in the malignant cells from 17 patients with myeloid neoplasms. Six patients had a primary myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML) de novo; ten patients had therapy‐related MDS and/or AML (t‐MDS/t‐AML), and one patient had chronic myelogenous leukemia in myeloid blast phase. Two of the six patients with MDS or AML de novo had extensive exposure to industrial so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 36 publications
4
22
1
Order By: Relevance
“…16 In this model deletions or loss of the short arm of chromosome 17 or loss of a whole chromosome 17 were secondary cytogenetic events. A dic(5p;17q) has previously been closely related to mutations of the p53 gene located at 17p13, and to a complex karyotype, 8 and our results support the latter association.…”
Section: Tablesupporting
confidence: 86%
See 1 more Smart Citation
“…16 In this model deletions or loss of the short arm of chromosome 17 or loss of a whole chromosome 17 were secondary cytogenetic events. A dic(5p;17q) has previously been closely related to mutations of the p53 gene located at 17p13, and to a complex karyotype, 8 and our results support the latter association.…”
Section: Tablesupporting
confidence: 86%
“…In previous studies of t-MDS and t-AML dicentric chromosomes have often been observed, and specific dicentric chromosomes such as the dic(1;7), 6,7 the dic(5;17), 8 and the dic(7;12) 9 have been discussed in separate reports. However, the occurrence of dicentric chromosomes has not been studied in general in a large series of patients with t-MDS and t-AML.…”
Section: Introductionmentioning
confidence: 99%
“…Dicentric chromosomes which have been identified in hematological malignancies include the recurrent dic(17;20) [36, 37] and dic(5;17) [38] in MDS and AML and the dic(9;20) in acute lymphoblastic leukemia [39], as well as a range of other abnormalities [3, 3941]. These are usually interpreted as unbalanced reciprocal translocations (see Figure 1), with breakpoints often described at or near the centromere [40, 42, 43].…”
Section: Dicentric Chromosomes In Malignancymentioning
confidence: 99%
“…19,20 Hematological malignancies may occur in patients with Seckel syndrome, in whom not only aberrant spliced transcript but also wild-type transcript of ATR are expressed, indicating that mutations of this gene may be involved in the pathogenesis of hematological malignancies in a dominant negative fashion. 23,35 Previous studies have also demonstrated that mice with heterozygous defects in ATR exhibit increased incidence of lymphoma. 19 In the present study, heterozygous frameshift and point mutations affecting the PI3K domain of ATR, 33 thus indicative of the loss-offunction mutation, were detected in two PAL lines.…”
Section: Discussionmentioning
confidence: 97%